Three-year growth trajectories and catch-up patterns in extremely low birth weight infants: a focus on early nutritional interventions - Soliman, Ashraf T; Alyafei , Fawzia; De Sanctis, Vincenzo; Alaaraj, Nada; Hamed, Noor; Ahmed, Shayma; Ali, Hamdy; Alkuwari, Mohamed (Acta Biomedica Atenei Parmensis, 2024)
Introduction: Growth trajectories of preterm infants, particularly those with extremely low birth weight (ELBW) defined as less than 750 grams, are notably complex and highly variable. Objective: We tracked the growth patterns of 35 ELBW infants born in a tertiary care facility, fed with preterm formula for the first 3-6 months of life. Results: ELBW infants showed significant initial deficits in weight, length, and head circumference, yet demonstrated considerable catch-up growth over 3 years. The initial mean weight-for-age Z-score (WAZ) was - 8.70, a stark deviation from the median of the reference population. By 36 months, the WAZ improved to -1.24, although 25.7% of infants continued to be underweight. The length-for-age Z-score (LAZ) began at -9.95, indicative of a pronounced deficiency in length, but by the third year, it had markedly improved to -0.35, with 11.4% of infants still measuring below the norm. The weight-for-length Z-score (WLZ) was initially -19.41, suggesting acute malnutrition; however, it fluctuated and improved to -1.75 by 36 months, with 31.4% of the cohort still at risk for malnutrition. Head circumference-for-age Z-score (HCZ) showed an initial value of -9.52 and improved to -1.75 by 36 months, but recovery in head growth was slower, with 6 out of 35 infants remaining below the reference curve.  Conclusion: Our findings reveal that ELBW infants exhibit significant improvements in WAZ, LAZ, WLZ, and HCZ over a period of three years, with most of the catch-up growth occurring within the first year, and LAZ continuing to improve into the third year.